Religious Language in Kalindaqdaq (Mandar): Lexicon and Metaphor in an Islamic Oral Tradition - Iqbal, Muhammad; Lampe, Munsi; M. Syaiful; Guntur, Ahmad Ismail; Wahyuni; Rahman, Ratna; Haedar, Razak (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2025)
Academic research on religious expression in Indonesia has long emphasized written sources, while it often overlooks oral traditions such as Kalindaqdaq, an oral poetry of the Mandar people that actively conveys Islamic teachings. This research gap appears because previous studies rarely examine how lexicon and metaphor operate linguistically within this tradition. This study therefore examines how Kalindaqdaq constructs religious values by combining philosophical, linguistic, and anthropological perspectives. This qualitative study analyzes Lontara manuscripts through philological methods, observes Kalindaqdaq performances ethnographically, and examines recorded performances using content analysis. The metrical analysis shows that performers consistently apply an 8-7-5-7 syllabic pattern in 98% of the verses. The lexical analysis reveals that Arabic theocentric terms account for 45% of the religious vocabulary and undergo systematic phonological adaptation. The metaphor analysis further demonstrates how conceptual metaphors translate abstract Islamic ideas into concrete Mandar cultural experiences. These findings show that the study contributes methodologically by combining Scheler’s value theory with systematic linguistic analysis of lexical and metaphorical patterns. At the empirical level, the study documents an endangered oral tradition and clarifies how Islamic doctrine interacts with local cultural cognition in Nusantara’s religious oral literature.